ANALISIS KEBUTUHAN MODEL SITUATIONAL JUDGMENT TEST DALAM UJI KOMPETENSI CALON KEPALA SEKOLAH - Yogi Satrio Aribowo; Tity Kusrina; Dewi Amaliah Nafiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Test (SJT) in the competency assessment of prospective school principals as an alternative to the conventional methods still predominantly used in Indonesia. The main issue addressed is the lack of assessment instruments capable of evaluating contextual competencies, which are crucial in the school leadership role. A descriptive qualitative approach was employed, with data collected through semi-structured interviews and questionnaires involving key educational stakeholders in Pemalang Regency. The results show that a majority of respondents (60% stated "necessary" and 40% "very necessary") consider the Situational Judgement Test (SJT) a relevant and important method to be applied in principal selection processes. The findings also indicate that Situational Judgement Test (SJT) is superior in assessing competencies such as decision-making, conflict resolution, and professional ethics—areas often overlooked by conventional testing methods. Therefore, Situational Judgement Test (SJT) is recommended as a more comprehensive assessment tool for evaluating educational leadership competencies.